PENGARUH KUALITAS PELAYANAN DAN FASILITAS KESEHATAN TERHADAP TINGKAT KEPUASAN PASIEN DI RUMAH SAKIT UMUM DAERAH (RSUD) DR. R. SOEDJATI SOEMODIARDJO PURWODADI KABUPATEN GROBOGAN - Nia Octaviani; Kasidin (Media Akuntansi, 2021)
ABSTRACT Improving the quality of service also needs to be done by health service units including hospitals. The hospital has a mission to provide quality health services that are affordable to the community in order to improve the public health status. This type of research used in this research is quantitative research. The sampling technique used was non probability sampling. This study used a sample of 100 (one hundred) respondents. The instrument testing technique in this study was validity and reliability tests, while the data analysis techniques used were descriptive analysis, multiple linear analysis, and classical assumption. The results showed that: 1) service quality had an effect on patient satisfaction, 2) facilities had no effect on patient satisfaction, 3) service quality and facilities had an effect on patient satisfaction.